Analytic salinity-temperature relations for the upper-thermocline waters of the eastern North Atlantic subtropical gyre - Marrero-Díaz, Ángeles; Rodríguez-Santana, Ángel; Machín, Francisco; Pelegrí, Josep Lluis (Scientia Marina, 2006)
We study the dependence of salinity on temperature in two by two degrees latitude-longitude boxes, for surface and upper-thermocline waters of the eastern North Atlantic subtropical gyre. The initial data set, from historical databases as well as from recent hydrographic cruises in the region, is carefully scrutinized to reject dubious measurements. We search for polynomial relations of variable degree between salinity and temperature, the optimal fit is selected as the polynomial with the lowest degree that satisfies several statistical criteria. An independent hydrographic cruise is used to confirm that the method performs substantially better than estimates from climatological data, and leads to relatively low deviations in geopotential anomaly and other derived quantities. An error propagation analysis using the Monte Carlo method shows equally good results.